Pandangan Masyarakat tentang Makam Syekh Siti Jenar di Semanding Tuban, Kemlaten dan Bukit Amparan Jati Cirebon: Kajian Sejarah Lisan - Roby Indra Muldiansyah (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstrak: This article aims to dissect the public's perspective on the mysterious Syekh Siti Jenar. This writing focuses on the views of the local community about the Tomb of Syekh Siti Jenar which is located in three regions in Indonesia, namely Semanding Tuban, Kemlaten and Bukit Amparan Jati Cirebon. This study uses the theory used in this study, namely the symbolic theory pioneered by Hebert Blumer. The methods used in this study are: Heuristics, Criticism, Interpretation and Data Validity. From the results of the study it was concluded that: (1) Syekh Siti Jenar, which so far was considered by some to be just a mythical figure in history, actually justified its existence based on field research which found genealogies and origins. (2) The teachings of Sheikh Siti Jenar are actually not heretical, in fact he is Ma'rifatullah who, according to sources of literacy, has more knowledge than the Wali. (3) The tomb of Syekh Siti Jenar is also controversial with the large number of tombs scattered across Indonesia, but the authors argue that so far the original tomb has not been found. Keywords: Syekh Siti Jenar, doctrine, grave